Tafsir Maqashid: Islamic Solutions to Generation Z's Mental Health Challenges - Zakaria, Aceng; Budi Setiawan; Solahudin; Sitinoramalina, Sitinoramalina (ZAD Al-Mufassirin, 2025)
This research addresses the growing mental health challenges faced by Generation Z, largely due to social pressures, technology dependency, and information overload. These issues necessitate relevant solutions, one of which may be found through a religious perspective. The aim of this study is to explore the role of Tafsir Maqashid, which emphasizes the core objectives of religion, such as preserving intellect (hifz al-'aql) and soul (hifz an-nafs), in providing solutions for mental health problems. The research employs a qualitative interpretative methodology, utilizing a literature review. The findings suggest that a deep religious understanding through Tafsir Maqashid offers a valuable and contextual spiritual framework for Generation Z to address their mental health challenges. This study contributes a new perspective on how religious understanding can be adapted to modern issues, particularly in supporting the mental well-being of Generation Z. The novelty of this research lies in applying Tafsir Maqashid as a relevant and contemporary approach to mental health care for Generation Z.